LINGUISTIC CHARACTERISTICS OF INTERNET SLANG ACROSS DIFFERENT LANGUAGE SYSTEMS: A COMPARATIVE STUDY - Askarova Durdona Shuhratjon kizi,Ubaydullayeva Maftunaxon Omonboy kizi (International Journal of Literature and Language Studies, 2026)
This article explores the linguistic characteristics of internet slang across different language systems, focusing on English, Japanese, and Uzbek digital communication as primary comparative examples. Internet slang represents a rapidly evolving linguistic phenomenon shaped by technological innovation, online communities, and cultural values. By analyzing phonological, morphological, syntactic, semantic, and pragmatic features of slang expressions, the study illustrates how digital users creatively manipulate language to achieve social bonding, identity construction, humor, and communicative efficiency. The article further highlights cross-linguistic similarities—such as abbreviation patterns, borrowing, and multimodal integration—and differences resulting from typological constraints, writing systems, orthography, and cultural norms.